2018
DOI: 10.1364/oe.26.015665
|View full text |Cite
|
Sign up to set email alerts
|

Transparent broadband metamaterial absorber enhanced by water-substrate incorporation

Abstract: In this paper, a transparent metamaterial absorber (MA) loaded with water substrate is presented, which can simultaneously achieve enhanced broadband microwave absorption and tunable infrared radiation. As a proof, the indium tin oxide (ITO) films are first introduced here as a frequency selective surface (FSS) on the top layer and reflective backplane on the ground layer. Next the distilled water combined with the polymethyl methacrylate (PMMA) substrate is employed as a hybrid substrate in the middle. Simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(40 citation statements)
references
References 22 publications
0
39
0
Order By: Relevance
“…The excellent stability under mechanical deformations can be ascribed to the inherent robust properties of the Ag NWs and the stretchable transparent substrate, which is the limitation of the commonly used indium tin oxide, graphene, or pure metal as the conductive layers and glass or polymethyl methacrylate as the substrates. 41,[54][55][56] In addition to the mechanical stability, the transparency of the fabricated absorbers was measured and is depicted in Fig. S10.…”
Section: Resultsmentioning
confidence: 99%
“…The excellent stability under mechanical deformations can be ascribed to the inherent robust properties of the Ag NWs and the stretchable transparent substrate, which is the limitation of the commonly used indium tin oxide, graphene, or pure metal as the conductive layers and glass or polymethyl methacrylate as the substrates. 41,[54][55][56] In addition to the mechanical stability, the transparency of the fabricated absorbers was measured and is depicted in Fig. S10.…”
Section: Resultsmentioning
confidence: 99%
“…Distilled water has a frequency-dispersive permittivity, which can be seen as a good candidates for broadband absorption. [89,131] Qu et al used water as the This article is protected by copyright. All rights reserved.…”
Section: Dielectric Layer Tailoringmentioning
confidence: 99%
“…As the meta-absorber field evolved, interesting designs with additional functionality have also emerged. Several studies have proposed optically transparent microwave absorbers by adopting a mesh grid [94], indium tin oxide [74,89], water substrate [95], or standing-up ring resonators [96], demonstrating the applicability to important window stealth and other applications. Some studies have demonstrated broadband absorbers that are easy to fabricate [97,98].…”
Section: Thin Meta-absorbers With Admittance Matching Layersmentioning
confidence: 99%